Establishment of Innovation Platforms (IPs) to facilitate the participation of livestock farmers in vaccination in Mali - CGIAR Research Program on Livestock (2019)
IPs were piloted by CARE International and a World Bank livestock development programmes in Mali and proved successful in fostering participation of farmers to vaccination in 35 communes.